Manajemen Sekolah Inklusif dalam Mengembangkan Softskill Siswa di SMP Negeri 7 Sawang Kabupaten Aceh Utara - Suriati Suriati; Sari Rizki; Hera Yanti (Journal on Education, 2024)
This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed descriptively in a qualitative manner. The findings reveal that inclusive education management at the school encompasses the planning, organizing, implementation, and evaluation of inclusive education programs. The principal plays a key role in ensuring that all components of inclusive education function effectively, from providing facilities to overseeing program implementation. The main challenges faced include limited resources and the need for more intensive teacher training to handle inclusive students. This research suggests enhancing cooperation between the school, the local community, and the government in the development of sustainable inclusive programs. The implication of this study is the importance of adaptive and inclusive leadership in creating a welcoming educational environment for all students, including those with special needs.